Interpretation of Society and Religion in Fiction - Xalilova Dilbar Jalilovna (Zien Journals, 2023)
In this article, it is analyzed that the interpretation of human and social issues in fiction is broadly revealed in psychological, social, philosophical, and domestic works.
Keywords: psychological imagination; man and society; faith